Innovation in Educational and Societal Transformation: The MacArthur Foundation, Jesuit Business Schools, and the World - Stoner, James A. F. (Archīum Ateneo, 2018)
On June 2, 2016, the MacArthur Foundation announced a competition awarding $100 million to a single project that would contribute toward solving a significant societal problem. Six weeks later, in Nairobi, Kenya, the members of the annual meeting of the International Association of Jesuit Business Schools’ World Forum unanimously passed a resolution requesting the submission of an application that utilized the resources of the global network of Jesuit business schools in addressing the inter-connected problem of global unsustainability, social injustice, and poverty. This article reports on the resulting 2016 application as well as on a possible 2019 version that builds upon it. The article emphasizes four aspects of innovation at the core of both these applications and the 2016 MacArthur Foundation competition. The four areas are: 1) the MacArthur Foundation’s innovative approach to inspiring societal change; 2) innovation in teaching and research content—transforming teaching materials and research topics in business schools, both Jesuit and other; 3) innovation in the processes of organizational transformation—participating business schools transforming their teaching and research in an “impossibly” short time period of only three years; and 4) innovation in the processes of societal transformation—achieving collaborative transformation among business schools, the business community, governmental agencies, spiritual and religious organizations, social enterprises, and not-for-profits.